Directives in teacher talk with primary school EFL learners: A study of five teachers in Croatia - Jakupčević, Eva (Neofilolog, 2025)
Teachers represent important pragmatic models for their students (Barón, et al., 2020). While teacher talk has been viewed as providing learners with a limited variety of pragmatic language (e.g., Nikula, 2002), there has also been evidence that it can be pragmatically attuned to the learners’ needs (Martí, Portolés, 2019). The present study is an analysis of directives in the teacher talk of five L1 Croatian teachers working with primary school EFL learners (aged 12/13). Five 45-minute EFL lessons were analysed, one for each teacher, with the aim of identifying and quantifying the occurrences of directives in instructional and regulative classroom discourse. A further qualitative analysis provides insight into how the teachers’ choice of directives relates to contextual matters in respect to their realisation (i.e., degree of directness, use of modifying strategies). The results are in line with previous studies, with teachers showing an overall preference for directness (e.g., Chen, Tseng, 2015; Liu, Hong, 2009). However, all of the teachers used directives to build interaction and scaffold their students’ language, while maintaining a relatively informal atmosphere, which may be linked to their choice of more direct forms. Ultimately, the highly diverse individual styles of the teachers seemed to be reflected most in their preference for particular forms.